THE INFLUENCE OF TEACHER COMPETENCE AND EDUCATIONAL FACILITIES ON TEACHING MOTIVATION OF PUBLIC JUNIOR HIGH SCHOOL TEACHERS IN ACEH BESAR REGENCY - Zulfia Rahmi; Ismail; Niswanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The role of teacher competence and educational facilities is crucial in enhancing teachers' teaching motivation at schools. Good teacher competence and educational facilities are capable of boosting teachers' motivation. The sample was taken using probability sampling technique, involving 84 teachers. The purpose of this research is to determine: (1) the influence of teacher competence on teaching motivation; (2) the influence of educational facilities on teaching motivation; (3) the simultaneous influence of teacher competence and educational facilities on teaching motivation. This research employs a quantitative correlational approach. Data collection techniques include observation, questionnaires, and documentation. The data analysis techniques used are validity test, reliability test, multiple linear regression analysis, simultaneous significance test (F-statistic test), coefficient of determination analysis (R2), and partial influence significance test (t-test). The results of this study indicate that: (1) there is a positive and significant influence of teacher competence on teaching motivation, with the tendency of teacher competence variables being in the high category by 35%; (2) there is a significant influence of educational facilities on teaching motivation, evidenced by the educational facilities variable being in the very high category by 71%; (3) there is a positive and significant simultaneous influence of teacher competence and educational facilities on teaching motivation, with a significance value of 0.001, F-value (30.082) > F-table (3.11), and p-value (0.001) < α (0.05). The coefficient of determination indicates an R square value of 0.426, and the equation notation Y = 36.412 + 0.283X1 + 0.055X2, meaning that the positive constant value suggests a positive influence of the independent variables, teacher competence and educational facilities, on teaching motivation.